Topological optimization of constructive solid geometry of lightweight structures - I. L. Kovaleva; D. P. Kunkevich; V. V. Naprasnikov; Y. V. Polozkov; A. A. Chvankov (Системный анализ и прикладная информатика, 2022)
The work is devoted to solving the problem of topological optimization in the design of lightweight structures. The advantages and disadvantages of popular topological optimization methods are analyzed. One of the characteristic problems of all methods is the dependence of their results on grid partitioning. Besides, there is a necessity to recast the geometry model of the structure. To solve this problem, it is proposed to perform the formation of cavities based on the ESO method directly at the constructive solid geometry from the shape elements. The main stages of the proposed approach are described, the use of clustering to simplify the shape of the surfaces of the formed cavities is justified.